High-density stretchable liquid metal-based biological electrode as well as preparation method and application thereof

By printing ink mixed with gallium-based liquid metal nanoparticles and metal nanosheets on a flexible substrate, using the acid environment to activate the circuit, the problem of uneven sintering of liquid metal circuits is solved, and the preparation of high-density, stretchable liquid metal-based bioelectrodes is achieved, and the resolution and accuracy of electrophysiological signal acquisition are improved.

CN119757490AActive Publication Date: 2025-04-04HARBIN INST OF TECH
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202510048682.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-04-04
Estimated Expiration
2045-01-13

AI Technical Summary

Technical Problem

Existing liquid metal circuits are difficult to efficiently and uniformly sinter, and the high-density and small-scale electrode arrays have poor stability under large strain conditions, resulting in low resolution and accuracy of electrophysiological signal acquisition.

Method used

The flexible substrate is prepared by adding α-ketoglutaric acid to butyl acrylate, and mixing the gallium-based liquid metal into nanoparticles with metal nanosheets to form ink. The liquid metal electrode is printed on the pre-stretched flexible substrate by stencil printing, and the circuit is activated using the acid environment to remove the oxide layer to achieve the connection of the conductive path.

Benefits of technology

The preparation of high-density, stretchable liquid metal-based bioelectrodes is achieved, with stable tensile conductivity and high resolution, and can stably collect electrophysiological signals under large strain conditions, avoid signal artifacts, and improve monitoring accuracy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119757490A_ABST
    Figure CN119757490A_ABST
Patent Text Reader

Abstract

The invention discloses a high-density stretchable liquid metal-based biological electrode as well as a preparation method and application thereof, and belongs to the technical field of biological electrode composite materials and preparation thereof. The technical problem that efficient and uniform sintering and high-resolution preparation of an existing liquid metal circuit are difficult is solved. According to the method, gallium-based liquid metal is prepared into liquid metal nanoparticles, then the liquid metal nanoparticles are mixed with metal nanosheets to serve as printing ink, an oxidation layer of the liquid metal nanoparticles is etched through acid, and the problem that the liquid metal nanoparticles are difficult to efficiently and uniformly sinter is solved. Alpha-ketoglutaric acid and butyl acrylate are used as raw materials to prepare the flexible substrate with good mechanical strength and tensile resilience, so that the binding force between the flexible substrate and the ink is effectively improved, and the preparation of the small-size high-density liquid metal-based biological electrode with stable tensile conductivity is realized; signal artifacts caused by resistance changes when the electrodes deform are avoided, and the resolution ratio and accuracy of electrophysiological signal collection are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a high-density, stretchable liquid metal-based bioelectrode and a preparation method and application thereof, belonging to the technical field of bioelectrode composite materials and preparation thereof. Background Art

[0002] Electrophysiological signals reflect various physiological activities of the human body. Monitoring electrophysiological signals helps to understand the encoding and operation mechanism of movement and perception processes in the human body, which is crucial for understanding and treating nerve or muscle dysfunction diseases. In order to obtain accurate data of electrophysiological signals, electrodes as interfaces between the human body and the device need to meet many requirements, such as low impedance, high density, stable stretch conductivity, good biocompatibility and fatigue resistance. However, at present, most bioelectrodes have the problems of low electrode stretchability and poor cyclic stretching stability.

[0003] Gallium-based liquid metal is the preferred material for preparing stretchable bioelectrodes due to its high conductivity and deformability, but the high surface energy of liquid metal makes it difficult to shape. It is worth noting that the oxide layer (Ga2O3) spontaneously formed on the surface of gallium-based liquid metal makes it possible to pattern it. One method is to disperse it into liquid metal micro-nanoparticles through simple mechanical processing technology, but because the Ga2O3 layer isolates the direct contact between the liquid metals, the circuit prepared based on this is usually not conductive, so it is necessary to destroy the Ga2O3 layer to make the liquid metal re-contact to form a conductive path (this process is also called "sintering"). Existing liquid metal sintering technology is difficult to achieve efficient and uniform sintering of high-density, small-scale electrode arrays. In addition, the lack of adhesion between the electrode and the tissue can also cause problems such as motion artifacts in the collected electrophysiological signals. Therefore, it is very necessary to provide a uniform and efficient liquid metal sintering technology, develop liquid metal-based bioelectrodes that can be conformally and tightly attached to human skin, and achieve high-resolution and stable monitoring of electrophysiological signals under large strain conditions, which is very necessary for applications in biomedical fields such as health monitoring, disease diagnosis and treatment, and body function research. Summary of the invention

[0004] In order to solve the technical problem that existing liquid metal circuits are difficult to sinter efficiently and evenly and prepare with high resolution, the present invention provides a high-density, stretchable liquid metal-based bioelectrode and a preparation method and application thereof.

[0005] The technical solution of the present invention:

[0006] One of the purposes of the present invention is to provide a method for preparing a high-density, stretchable liquid metal-based bioelectrode, the method comprising the following steps:

[0007] (1) Preparation of flexible substrates;

[0008] Adding α-ketoglutaric acid to butyl acrylate, stirring at room temperature until completely dissolved, thereby obtaining a base glue; after the base glue is laid as a film, curing it with ultraviolet radiation, thereby obtaining a polyacrylate flexible substrate;

[0009] (2) Preparation of ink;

[0010] The liquid metal and the solvent are mixed and ultrasonically treated in an ice water bath to obtain liquid metal nanoparticles; the liquid metal nanoparticles are then mixed with metal nanosheets and stirred evenly to obtain ink;

[0011] (3) Printing of ink;

[0012] Printing the ink obtained in step (2) on the surface of a pre-stretched polyacrylate flexible substrate using a stencil printing process to obtain a liquid metal electrode;

[0013] (4) Sintering of liquid metal circuits;

[0014] Placing the liquid metal electrode obtained in step (3) in an acid environment to activate the circuit, washing the electrode multiple times to remove the acid remaining on the surface, and then drying the electrode to obtain a conductive electrode;

[0015] (5) Encapsulation of recording points;

[0016] Dissolving acrylic acid, α-ketoglutaric acid and polyethylene glycol diacrylate in a eutectic solvent of glycerol and choline chloride, stirring until completely dissolved, to obtain an ion gel precursor solution; dropping the ion gel precursor solution on the recording site, curing it by ultraviolet irradiation, and completing the encapsulation of the recording site;

[0017] (6) Encapsulation of conductive paths;

[0018] After connecting the conductive electrode interface with a wire, base glue is used to encapsulate the conductive path except the recording site, and then cured by ultraviolet irradiation to obtain a liquid metal-based biological electrode.

[0019] It is further defined that the mass ratio of α-ketoglutaric acid added to butyl acrylate in (1) is (0.01-0.5):10.

[0020] It is further defined that the UV curing time in (1) is 15 minutes.

[0021] It is further defined that the liquid metal in (2) is one or more of gallium-based liquid metals, and the solvent is n-decanol, ethanol, acetone or water; and the mass ratio of the liquid metal to the solvent is 1:(1-5).

[0022] Further defined, the liquid metal consists of 75.5 wt % gallium and 24.5 wt % indium.

[0023] It is further defined that the metal nanosheets in (2) are copper, silver, nickel or gold with a particle size of 1 to 10 μm; and the mass ratio of liquid metal nanoparticles to metal nanosheets is 20:(1 to 3).

[0024] It is further defined that the ultrasonic treatment in (2) uses a cell disruptor with a power of 100 to 750 W and a time of 5 to 10 min.

[0025] It is further defined that in (3), the pre-stretching strain of the polyacrylate flexible substrate is 0 to 400%.

[0026] It is further defined that the template printing process in (3) is screen printing or hollow template printing.

[0027] Further defined, (4) the medium acid environment is the acid mist volatilized from concentrated hydrochloric acid with a concentration of 36-38 wt.% or a dilute hydrochloric acid solution with a concentration of 2-4 wt.%; and the treatment time in the acid environment is 10-200 s.

[0028] It is further defined that the solvents used for rinsing in (4) are ethanol and deionized water.

[0029] It is further defined that the drying temperature in (4) is 50-80°C.

[0030] Further defined, (5) the ion gel precursor solution comprises 30-40 wt.% glycerol, 20-40 wt.% choline chloride, 10-50 wt.% acrylic acid, 0.2-1 wt.% α-ketoglutaric acid, and 0.1-1 wt.% polyethylene glycol diacrylate.

[0031] It is further defined that the preparation temperature of the glycerol and choline chloride eutectic solvent in (5) is 100° C. and the preparation time is 2 h.

[0032] It is further defined that the volume of the ion gel precursor solution added to each recording site in (5) is 2 μl.

[0033] It is further defined that the UV curing time in (5) is 3 to 10 minutes.

[0034] The second object of the present invention is to provide a high-density, stretchable liquid metal-based bioelectrode prepared by the above method.

[0035] The third object of the present invention is to provide an application of the above-mentioned high-density, stretchable liquid metal-based bio-electrode, specifically for collecting electrophysiological signals from the surface of a biological body.

[0036] Beneficial effects of the present invention:

[0037] The present invention first prepares gallium-based liquid metal into liquid metal nanoparticles, then mixes the liquid metal nanoparticles with metal nanosheets to obtain ink, which is printed on a pre-stretched flexible substrate surface using a stencil printing process, and a high-density liquid metal electrode is obtained after the strain is released. The oxide layer of the liquid metal nanoparticles is etched with acid to make the liquid metals contact with each other to achieve circuit connectivity, thereby solving the problem that liquid metal nanoparticles are difficult to sinter efficiently and uniformly.

[0038] The present invention uses α-ketoglutaric acid and butyl acrylate as raw materials to prepare a flexible substrate with good mechanical strength and tensile resilience, while effectively improving the bonding strength between the flexible substrate and the ink, realizing the preparation of a small-sized, high-density liquid metal-based bioelectrode with stable tensile conductivity, avoiding signal artifacts caused by resistance changes when the electrode is deformed, and improving the resolution and accuracy of electrophysiological signal acquisition.

[0039] In addition, the preparation method provided by the present invention is low-cost, simple to operate, and has high production efficiency. The prepared electrode has the advantages of high resolution, low impedance, good tensile conductivity and long-term stability, and can achieve high-quality monitoring of human electrophysiological signals. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 is the stress-strain curve of the flexible substrate prepared in Example 1;

[0041] Figure 2 This is a microscope image of the liquid metal electrode (before sintering) prepared in Example 1;

[0042] Figure 3 This is a microscope image of the liquid metal electrode (after sintering) prepared in Example 1;

[0043] Figure 4 This is a scanning electron microscope image of a high-resolution conductive circuit with a line width of 150 μm prepared in Example 1;

[0044] Figure 5 Optical photographs of conductive circuits with different line widths prepared in Example 1;

[0045] Figure 6 The tensile conductivity of the liquid metal-based bioelectrode prepared in Example 1;

[0046] Figure 7 The tensile conductivity of the liquid metal-based bioelectrode prepared in Comparative Example 1;

[0047] Figure 8 The resistance change curve of the liquid metal-based bioelectrode prepared in Example 1 after cyclic stretching for 5000 times at 100% strain;

[0048] Fig. 9 This is a comparison diagram of electrochemical impedance of the recording site of the liquid metal-based bioelectrode prepared in Example 1 before and after ion gel encapsulation;

[0049] Fig.10 The electromyographic signal collected by the liquid metal-based bioelectrode prepared in Example 1;

[0050] Fig.11 This is a comparison chart of the adhesion between the ink prepared in Example 1 and a polybutyl acrylate (BA) flexible substrate and an Ecoflex flexible substrate. DETAILED DESCRIPTION

[0051] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0052] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, methods and instruments used are conventional materials, reagents, methods and instruments in the art unless otherwise specified, and can be obtained through commercial channels by those skilled in the art.

[0053] Example 1

[0054] The method for preparing a high-density, stretchable liquid metal-based bio-electrode provided in this embodiment comprises the following steps:

[0055] Step 1, preparation of ink:

[0056] First, 5 g of gallium-indium alloy (EGaIn, 75.5 wt% Ga and 24.5 wt% In) was mixed with 20 g of n-decanol solvent, the mixed liquid was placed in an ice-water bath, and ultrasonicated for 5 min at a power of 750 W using a cell disruptor. The ultrasonicated mixed liquid was allowed to stand and precipitated to obtain liquid metal nanoparticles; then, 10 g of the liquid metal nanoparticles was evenly mixed with 0.7 g of copper nanosheets with a particle size of 10 μm to obtain a printable ink.

[0057] Step 2: Preparation of flexible substrate:

[0058] First, weigh 0.1 g of α-ketoglutaric acid and add it to 10 g of butyl acrylate solution, and stir at room temperature until it is completely dissolved to obtain a mixed solution;

[0059] Then, the mixture was spread on the surface of silicone oil paper (thickness 200 μm) and illuminated with 107 mW / cm 2 The cross-linking and curing was carried out by ultraviolet irradiation for 15 minutes to obtain a polybutyl acrylate (BA) flexible substrate.

[0060] The mechanical properties of the obtained flexible substrate were characterized, and the specific stress-strain curves were as follows: Figure 1 As shown by Figure 1 It can be seen that the flexible substrate prepared as above has good mechanical strength and tensile resilience.

[0061] Step 3, preparation of electrodes:

[0062] First, the ink obtained in step one is printed on the surface of the flexible substrate obtained in step two using a screen printing process, and then placed in a 60° C. oven for treatment to evaporate the solvent, thereby obtaining a liquid metal electrode.

[0063] Then, the dried liquid metal electrode is placed in an acid environment (acid mist volatilized from concentrated hydrochloric acid with a mass concentration of 36-38 wt.%) for treatment for 60 seconds.

[0064] The microstructure of the liquid metal electrode before and after acid treatment was characterized. Figure 2 and Figure 3 As shown. Figure 2 It can be seen that the liquid metal nanoparticles before acid treatment are independent spherical due to the presence of the oxide layer (Ga2O3). Figure 3 It can be seen that after being treated under acidic conditions, Ga2O3 is removed and the internal liquid metals are interconnected to form a conductive path.

[0065] By pre-stretching the flexible substrate, the preparation of high-resolution conductive paths can be achieved. Specifically, before printing, the flexible substrate is pre-stretched to strains of 0%, 100%, 200% and 300%, respectively, to achieve the following: Figure 4 and Figure 5 Fabrication of conductive pathways with line widths of 600 μm, 300 μm, 200 μm, and 150 μm are shown.

[0066] Finally, the sintered electrode was washed several times with ethanol and deionized water to remove the acid remaining on the electrode surface, and then dried in an oven at 60°C to obtain a conductive electrode.

[0067] Step 4: Encapsulation of recording sites:

[0068] First, a mixture of 3.9 g of glycerol and 3 g of choline chloride was heated and stirred at 100° C. for 2 h until completely dissolved, to obtain a eutectic solvent of glycerol and choline chloride;

[0069] Then, 3.5 g of acrylic acid, 0.01 g of polyethylene glycol diacrylate and 0.1 g of α-ketoglutaric acid were added to 2.75 g of the eutectic solvent of glycerol and choline chloride, and the mixture was stirred until dissolved to form an ion gel precursor solution;

[0070] Finally, 2 μl of ion gel prepolymer was taken with a pipette and dropped onto the recording site of the conductive electrode (line width 600 μm) and placed under 107 mW / cm 2 Irradiate under UV light for 5 minutes to cross-link and solidify it, completing the encapsulation of the recording site.

[0071] Step 5: Encapsulation of Conductive Paths

[0072] After connecting the wire to the interface of the conductive electrode, evenly spread the base gel in the conductive path of the conductive electrode except the recording site, and then use 107mW / cm 2 The liquid metal-based bioelectrode was obtained by cross-linking and curing the bioelectrode under ultraviolet irradiation for 15 minutes, thereby completing the encapsulation of the bioelectrode conductive pathway.

[0073] Comparative Example 1

[0074] The difference between this comparative example and Example 1 is that a non-sticky (Ecoflex) substrate is used instead of the flexible substrate obtained in step 2. Specifically, part A and part B of the Ecoflex elastomer are mixed in equal mass ratios, evenly coated on a glass plate, and placed in an oven at 60°C for 20 minutes to solidify it to obtain a flexible substrate. The remaining process steps and parameter settings are the same as those in Example 1.

[0075] Effect example

[0076] (1) The two ends of the liquid metal-based bioelectrodes (line width 600 μm) prepared in Example 1 and Comparative Example 1 were clamped by an electronic universal testing machine and connected to a digital source meter through copper wires, and the resistance changes of the electrodes under different strain conditions were recorded at a constant output voltage of 1 V. The test results are shown in FIG. Figure 6 and Figure 7 As shown in the figure, it can be seen that due to the interfacial adhesion of the polybutyl acrylate (BA) flexible substrate prepared in Example 1 to the liquid metal, the tensile conductivity of the electrode prepared on the polybutyl acrylate (BA) substrate is better than that of the non-adhesive (Ecoflex) substrate.

[0077] (2) The liquid metal-based bioelectrode prepared in Example 1 was subjected to 100% strain cyclic stretching for 5000 times. The resistance change during the stretching process was as follows: Figure 8 As shown in the figure, it can be seen that the liquid metal-based bioelectrode prepared in Example 1 has high reliability and fatigue resistance, providing a guarantee for long-term and effective monitoring of human electrophysiological signals.

[0078] (3) The alternating current impedance test was used to test the relationship between the interface impedance of the electrodes before and after the encapsulation of the recording site in Example 1 and the frequency. The test results are as follows: Fig. 9 As shown in the figure, it can be seen that in 1~10 4Within the scanning frequency range of Hz, the electrode has a lower interface impedance after the recording site is encapsulated by ion gel, which will help the electrode obtain higher quality electrophysiological signals.

[0079] (4) The liquid metal-based bioelectrode prepared in Example 1 was placed on the skin surface of the human forearm to collect epidermal electromyographic signals. The results are as follows: Fig.10 As shown in the figure, it can be seen that the multi-channel electrodes can successfully collect electromyographic signals. Even after multiple muscle contractions, the electrodes always maintain stable and high-quality recordings, proving the feasibility of applying the electrode in human-computer interaction, rehabilitation medicine, or sports training.

[0080] (5) Use an electronic universal testing machine to test the adhesion strength between the ink and different substrates, record the maximum force of the ink falling off the substrate, use ImageJ software to calculate the area of ​​the ink falling off, and use the maximum force per unit area as the embodiment of the adhesion. The test results are shown in Fig.11 It can be seen that the adhesion between the flexible substrate of polybutyl acrylate (BA) prepared in Example 1 and the ink is much greater than that of the non-adhesive (Ecoflex) substrate.

[0081] The above description is only a preferred embodiment of the present invention. In view of the fact that technicians in the field of the present invention can make appropriate changes and modifications to the above implementation, the present invention is not limited to the specific implementation described above. Some modifications and changes to the present invention should also fall within the scope of protection of the claims of the present invention.

Claims

1. A method for preparing a liquid metal-based bioelectrode, characterized in that: include: (1) Preparation of flexible substrates; Add α-ketoglutaric acid to butyl acrylate, and stir at room temperature until completely dissolved to obtain a base glue; After the base glue is laid as a film, it is cured by ultraviolet irradiation to obtain a polyacrylate flexible base; (2) Preparation of ink; The liquid metal and the solvent are mixed and ultrasonically treated in an ice water bath to obtain liquid metal nanoparticles; the liquid metal nanoparticles are then mixed with metal nanosheets and stirred evenly to obtain ink; (3) Printing of ink; Printing the ink obtained in step (2) on the surface of a pre-stretched polyacrylate flexible substrate using a stencil printing process to obtain a liquid metal electrode; (4) Sintering of liquid metal circuits; Placing the liquid metal electrode obtained in step (3) in an acid environment to activate the circuit, washing the electrode multiple times to remove the acid remaining on the surface, and then drying the electrode to obtain a conductive electrode; (5) Encapsulation of recording points; Dissolving acrylic acid, α-ketoglutaric acid and polyethylene glycol diacrylate in a eutectic solvent of glycerol and choline chloride, stirring until completely dissolved, to obtain an ion gel precursor solution; dropping the ion gel precursor solution on the recording site, curing it by ultraviolet irradiation, and completing the encapsulation of the recording site; (6) Encapsulation of conductive paths; After connecting the conductive electrode interface with a wire, base glue is used to encapsulate the conductive path except the recording site, and then cured by ultraviolet irradiation to obtain a liquid metal-based bioelectrode.

2. The method according to claim 1, characterized in that The mass ratio of α-ketoglutaric acid added to butyl acrylate in (1) is (0.01-0.5):

10.

3. The method according to claim 1, characterized in that (2) The liquid metal is one or more of gallium-based liquid metals, and the solvent is n-decanol, ethanol, acetone or water; the mass ratio of the liquid metal to the solvent is 1:(1-5).

4. The method according to claim 1, characterized in that: (2) The metal nanosheets are copper, silver, nickel or gold with a particle size of 1 to 10 μm; the mass ratio of liquid metal nanoparticles to metal nanosheets is 20:(1 to 3).

5. The method according to claim 1, characterized in that (3) The pre-stretching strain of the pre-stretched polyacrylate flexible substrate is 0 to 400%.

6. The method according to claim 1, characterized in that (4) The medium acid environment is the acid mist volatilized by concentrated hydrochloric acid with a concentration of 36 to 38 wt.% or a dilute hydrochloric acid solution with a concentration of 2 to 4 wt.%; the treatment time in the acid environment is 10 to 200 seconds.

7. The method according to claim 1, characterized in that (5) The obtained ion gel precursor solution contains 30-40 wt.% glycerol, 20-40 wt.% choline chloride, 10-50 wt.% acrylic acid, 0.2-1 wt.% α-ketoglutaric acid, and 0.1-1 wt.% polyethylene glycol diacrylate.

8. The method according to claim 1, characterized in that The preparation temperature of the glycerol and choline chloride eutectic solvent in (5) is 100°C and the preparation time is 2h.

9. A high-density, stretchable liquid metal-based bioelectrode prepared by the method according to any one of claims 1 to 8.

10. An application of the high-density, stretchable liquid metal-based bioelectrode according to claim 9, characterized in that: Used to collect electrophysiological signals from the surface of biological bodies.

Citation Information

Patent Citations

  • Stretching conductive liquid metal particle based conductive ink and preparation method and application thereof

    CN108384327A

  • Self-adaptive liquid metal electrode with high stretchability and preparation of self-adaptive liquid metal electrode

    CN113593751A

  • Preparation method and application of flexible electronic material based on metal phase change

    CN114854198A

  • Fully-flexible and stretchable liquid metal-based biological electrode and preparation method and application thereof

    CN116110636A

  • Bio-based water-based acrylic acid hydrogel and preparation method thereof

    CN116622090A